Chest Computed Tomography Manifestation of Coronavirus Disease 2019 (COVID-19) in Patients With Cardiothoracic Conditions. Issue 4 (July 2020) - Salehi, Sana; Abedi, Aidin; Radmard, Amir Reza; Sorouri, Majid; Gholamrezanezhad, Ali
Abstract : The coronavirus disease 2019 (COVID-19) pandemic is a serious public health concern, with an exponentially growing number of patients worldwide. Computed tomography (CT) has been suggested as a highly sensitive modality for the diagnosis of pulmonary involvement in the early stages of COVID-19. The typical features of COVID-19 in chest CT include bilateral, peripheral, and multifocal ground-glass opacities with or without superimposed consolidations. Patients with underlying medical conditions are at higher risks of complications and mortality. The diagnosis of COVID-19 on the basis of the imaging features may be more challenging in patients with preexisting cardiothoracic conditions, such as chronic obstructive pulmonary disease, interstitial lung disease, cardiovascular disease, and malignancies with cardiothoracic involvement. The extensive pulmonary involvement in some of these pathologies may obscure the typical manifestation of COVID-19, whereas other preexisting pathologies may resemble the atypical or rare CT manifestations of this viral pneumonia. Thus, understanding the specific CT manifestations in these special subgroups is essential for a prompt diagnosis.